2002
DOI: 10.1039/b105735a
|View full text |Cite
|
Sign up to set email alerts
|

A ferrimagnetic cyclic tetranuclear copper(ii) complex: cyclo-[tetrakis(μ-η3-hydroxyethanoato-1κO:2κ2O′,O″)tetrakis(1,10-phenanthroline)tetracopper] tetranitrate dihydrate. Structural and magnetic properties

Abstract: The crystal structure and magnetic analysis of a cyclic tetranuclear copper() complex with formula [Cu 4 (phen) 4 (glyOH) 4 ](NO 3 ) 4 ؒ2H 2 O, where phen = 1,10-phenanthroline and glyOH = glycolate are described. Copper atoms are connected through bridging carboxylate groups from chelated glycolate units, forming a butterfly-type framework. Magnetic measurements as a function of temperature (2-300 K) and at 10, 100 and 1000 G were performed. The behaviour of the χ --T -T curves is characteristic of ferrimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Table 1 Main absorption bands in the infrared and tentative assignments of the corresponding vibrational modes of free ligands (H, hydrolysate; F, filtrate; R, retentate and WPI, whey protein isolate) and their respective iron complexes, obtained from FeCl 2 (eFe C) or FeSO 4 (eFe S). Sources for assignment to vibrational modes: (Acevedo-Chávez, Costas, Bernès, Medina, & Gasque, 2002;Barth, 2007;Benaki et al, 1998;Berova, Polavarapu, Nakanishi, & Woody, 2012;Chaud et al, 2002;Eckert et al, 2016;Huang et al, 2011;Kaiden, Matsui, & Tanaka, 1987;Krimm & Bandekar, 1986;Lee et al, 2015;Mukherjee, Chowdhury, & Gai, 2007;Nakamoto, 2009;O'Loughlin et al, 2015;Prigogine & Rice, 2009;Trivedi & Vasudevan, 2007 3. Results and discussion…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 Main absorption bands in the infrared and tentative assignments of the corresponding vibrational modes of free ligands (H, hydrolysate; F, filtrate; R, retentate and WPI, whey protein isolate) and their respective iron complexes, obtained from FeCl 2 (eFe C) or FeSO 4 (eFe S). Sources for assignment to vibrational modes: (Acevedo-Chávez, Costas, Bernès, Medina, & Gasque, 2002;Barth, 2007;Benaki et al, 1998;Berova, Polavarapu, Nakanishi, & Woody, 2012;Chaud et al, 2002;Eckert et al, 2016;Huang et al, 2011;Kaiden, Matsui, & Tanaka, 1987;Krimm & Bandekar, 1986;Lee et al, 2015;Mukherjee, Chowdhury, & Gai, 2007;Nakamoto, 2009;O'Loughlin et al, 2015;Prigogine & Rice, 2009;Trivedi & Vasudevan, 2007 3. Results and discussion…”
Section: Discussionmentioning
confidence: 99%
“…At 1431 cm − 1 , for the complexes with both iron sources, the appearance of an important band associated with the symmetric stretching vibration of the FeeCOO bond (Acevedo-Chávez et al, 2002) was observed. In addition, the shift in the ν s CeO bands from 1110-1039 (H and F) to 1117 cm − 1 in the complexes indicates the formation of FeeOeC bonds (Chaud et al, 2002;Huang et al, 2011).…”
Section: (I) Iron Coordination By the Ligandsmentioning
confidence: 98%
“…The average deviation of each Ga III atom from the mean plane formed by the four metal ions is 0.26 Å , while the GaÁ Á ÁGaÁ Á ÁGa angle, and the torsion angle between the four Ga III atoms are 83.21°and 38°, respectively. This topology is better described as ''butterfly'' [68] rather than square (Fig. 6).…”
Section: Description Of Structuresmentioning
confidence: 98%
“…Today the biomedical interest of gallium(III) complexes originates from the incorporation of its radionuclides ( 67 Ga 3+ , 68 Ga 3+ ) into diagnostic radiopharmaceuticals [58], the strong antitumour activity of GaCl 3 and Ga(NO 3 ) 3 which have been tested in cancer patients [59], and from the moderate in vitro anti-HIV (human immunodeficiency virus) activity of Ga(NO 3 ) 3 and some GaCl 3 /L complexes (L = various azoles) [60]. Our interest in the bioinorganic chemistry of Ga(III) is primarily focused on the preparation, structural and physical characterization, and evaluation of the biological activity of Ga(III) complexes with biologically relevant ligands [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, tetranuclear copper(II) clusters have been extensively studied. There are various Cu 4 structural forms: butterfly type [7,8], cyclic [9], roof-shaped dimer [10], cubane [11Ϫ14] and Cu 4 O 4 ring [15]. The introduction of hydroxyl groups is useful for assembling clusters, and small changes in structure may have large effects on the magnetic properties of these complexes.…”
Section: Introductionmentioning
confidence: 99%